Community service at Sanggar Belajar Cakrawangsa in Kucur Village, Dau Subdistrict, Malang - Ounu Zakiy Sukaton; Melany Melany; Lilis Lestari Wilujeng (University of Merdeka Malang, 2022)
Kucur Village, located in Dau District, Malang Regency, is a village that has a lot of potential. However, the economic condition of most of its residents is still far from prosperous. Through this community service activity, the Ma Chung University community service team aims to develop the potential and empower the young generation in Kucur Village through practical English language basic education in collaboration with the Sanggar Belajar Cakrawasa as a partner. The three main problems faced by the partner are limited teaching staff, monotonous learning activities, and unavailability of English learning modules. The methods offered as solutions to the three problems are providing the Training of Trainers (ToT) program to Ma Chung University students to volunteer as additional teaching staff to the partner, according to the Teaching English for Young Learners (TEYL) theory, using fun learning techniques, develop learning modules. After 8 months of mentoring, the three main partners' problems were finally resolved.